2023
DOI: 10.1161/circresaha.123.323030
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell MyD88 Is a Novel Regulator of Cardiac Fibrosis Through Modulation of T-Cell Activation

Abstract: BACKGROUND: Cardiac inflammation in heart failure is characterized by the presence of damage-associated molecular patterns, myeloid cells, and T cells. Cardiac damage-associated molecular patterns provide continuous proinflammatory signals to myeloid cells through TLRs (toll-like receptors) that converge onto the adaptor protein MyD88 (myeloid differentiation response 88). These induce activation into efficient antigen-presenting cells that activate T cells through their TCR (T-cell receptor). T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…T-cell receptor engagement, antigenic stimuli, tissue microenvironment, and metabolic reprogramming shape the repertoire of T cells into that of T helper cells (Th1, Th2, Th9, Th17, and Th22), cytotoxic T lymphocytes (CTLs), regulatory T (T reg ) cells, and natural killer T (NKT) cells ( Zhang and Zhang, 2020 ) . Induction of T cells by cardiac DAMPs processed by antigen-presenting cells results in cardiotropism, transformation of cardiac fibroblasts, and maladaptive cardiac remodeling ( Bayer et al, 2023 ) ( Figure 2 ). An increasing body of literature indicates that distinct subpopulations of T lymphocytes play a substantial role in the direct stimulation of fibroblasts and progression of cardiac fibrosis ( Nevers et al, 2015 ; Li et al, 2017 ; Abdullah and Jin, 2018 ) .…”
Section: Contribution Of the Immune System To Cardiac Homeostasismentioning
confidence: 99%
“…T-cell receptor engagement, antigenic stimuli, tissue microenvironment, and metabolic reprogramming shape the repertoire of T cells into that of T helper cells (Th1, Th2, Th9, Th17, and Th22), cytotoxic T lymphocytes (CTLs), regulatory T (T reg ) cells, and natural killer T (NKT) cells ( Zhang and Zhang, 2020 ) . Induction of T cells by cardiac DAMPs processed by antigen-presenting cells results in cardiotropism, transformation of cardiac fibroblasts, and maladaptive cardiac remodeling ( Bayer et al, 2023 ) ( Figure 2 ). An increasing body of literature indicates that distinct subpopulations of T lymphocytes play a substantial role in the direct stimulation of fibroblasts and progression of cardiac fibrosis ( Nevers et al, 2015 ; Li et al, 2017 ; Abdullah and Jin, 2018 ) .…”
Section: Contribution Of the Immune System To Cardiac Homeostasismentioning
confidence: 99%
“…116 The effects of MyD88 in the postinfarction inflammatory response may involve actions on several different cell types, including bone marrow-derived leukocytes, 117 resident cardiac macrophages, 118 cardiomyocytes, 115 and fibroblasts. 57 A recent study in a model of left ventricular pressure overload suggested important regulatory effects of MyD88 on T lymphocyte phenotype 119 ; however, the significance of these actions in MI has not been investigated. Endosomal TLR4 or TLR3 can also transduce proinflammatory signaling through MyD88-independent pathways, by recruiting another cytoplasmic adaptor protein called TRIF (TIR domain-containing adaptor inducing IFN [interferon]-β).…”
Section: Downstream Pathways Activated By Prrs: a System Of Adaptor M...mentioning
confidence: 99%